Hubungan Tingkat Pengetahuan Dengan Sikap Tentang Bahaya Rokok Elektrik Pada Pemuda/Remaja Majelis GKE Galilea - Jonathan Frederick Uda; Karmitasari YK; Dwi Agustian FI (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Smoking is a problem that cannot be resolved until now, various impacts and dangers of smoking have actually been published to the public, but this smoking habit is still difficult to stop (Indra et al.2015). Electronic cigarettes are synonymous with the terms vape personal vaporizer (PV), e-cigs, vapor, electrosmoke, green cig, smartcigarette (BPOM, 2015). Research Objectives: Aiming to determine the relationship between knowledge level and attitude about the dangers of e-cigarettes in youth / adolescents of the Galilee GKE Assembly. Research Methods: This type of research is correlational using Cross sectional. In this study, sampling was carried out by means of total sampling using the Spearman Rank statistical test. The sample in this study were youth / adolescents who were members of the Galilee GKE Assembly totaling 60 respondents using a measuring instrument, namely a questionnaire. Research Results: The results of the Spearman rank test obtained a correlation coefficient of 0.753**. This means that the level of strength of the relationship (correlation) between variables is 0.753 strong relationship so that there is a relationship between knowledge and attitude about the dangers of e-cigarettes in youth / adolescents of the Galilee GKE Assembly. Conclusion: There is a significant relationship between the level of knowledge and attitudes about the dangers of e-cigarettes in youth / adolescents of the Galilee GKE assembly.